Acknowledgments, The Livestock and Meat Industry Council, Inc. (Kansas Agricultural Experiment Station Research Reports, 2016)
Listed below are individuals, organizations, and firms that have contributed to the beef research program through financial support, product donations, or services. We appreciate your help!
Keywords: Acknowledgments